Potassium Alum Vaginal Suppository: Irritation Assessment in Rabbit - Sareh Sangy; Mojgan Tansaz; Homa Hajimehdipoor*; Leila Ara; Samira Sangy; Mehdi Mazinani (Iranian Society of Pharmacognosy, 2024)
Background and objective: Potassium alum, called "Zaj-e-abyaz" in Iranian traditional medicine, is used vaginally in traditional clinics as an astringent agent for uterine fibroids. Before evaluating its efficacy, it is necessary to prepare a suitable dosage form and assess the possible irritation in animal model which was the aim of the current research. Methods: Vaginal suppositories were prepared using 400 mg potassium alum, 200 mg honey and different proportions of poly ethylene glycol (PEG) 600, 1000 and 4000 in each suppository. The best formulation was used for evaluation of possible irritation in rabbit. The suppositories were used in rabbit's perineum daily for 5 consecutive days in 3 albino rabbits and the appearance of the vaginal opening and perineum for signs of erythema and edema were recorded every day. The final results were calculated as a primary irritation index (PII). Results: The best formulation contained potassium alum 20%, honey 10%, PEG 600 18%, PEG 1000 12%, PEG 4000 30% and water 10%. According to the animal test, the irritation of the vaginal mucus membrane was considered moderate in rabbits. Conclusion: Regarding the results, potassium alum could not be used in form of suppository in PEG vehicle and other formulations should be prepared for acquiring the least irritation.